2023
DOI: 10.1002/ncp.10976
|View full text |Cite
|
Sign up to set email alerts
|

Early vs delayed enteral nutrition or parenteral nutrition in hospitalized patients: An umbrella review of systematic reviews and meta‐analyses of randomized trials

Abstract: We conducted an umbrella review to summarize the existing evidence on the effect of early enteral nutrition (EEN) compared with other approaches, including delayed enteral nutrition (DEN), parenteral nutrition (PN), and oral feeding (OF) on clinical outcomes in hospitalized patients. We performed a systematic search up to December 2021, in MEDLINE (via PubMed), Scopus, and Institute for Scientific Information Web of Science. We included systematic reviews with meta-analyses (SRMAs) of randomized trials investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…The absence of EN induces a distinct change in the mucosal architecture, which impairs the gastrointestinal barrier [3]. Early EN (EEN) effectively reduces the incidence of infectious complications because EN maintains intestinal immune function [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of EN induces a distinct change in the mucosal architecture, which impairs the gastrointestinal barrier [3]. Early EN (EEN) effectively reduces the incidence of infectious complications because EN maintains intestinal immune function [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have demonstrated that earlier enteral nutrition can protect human intestinal epithelial barrier function ( 15 , 16 ). For hospitalized patients, early enteral nutrition may be beneficial ( 17 ). A recent study found that early administration of enteral nutrition reduces the incidence of ventilator-associated pneumonia in patients with severe trauma who require invasive ventilation ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have demonstrated that earlier enteral nutrition can protect human intestinal epithelial barrier function [15,16]. For hospitalized patients, early enteral nutrition may be beneficial [17]. A recent study found that early administration of enteral nutrition reduces the incidence of ventilator-associated pneumonia in patients with severe trauma who require invasive ventilation [18].…”
Section: Introductionmentioning
confidence: 99%